Direitos fundamentais sociais e controle judicial - Lage, Lívia Regina Savergnini Bissoli (2010)
The present thesis aims to analyze the creative role of the Judiciary in the Democratic Constitutional State in what it refers to the basic social rights accomplishment, through policies. Therefore, is judges duty’s the guard of the Constitution, which not only express the real factors of power, but must have a normative force able to change the ontological reality. After all, a democracy is not composed only by its transitory majorities, being very important the protection of those minorities also supported by the constitutionals clauses. Thus, the Judiciary must control the performance of the other branches, throughout the checks and balances system in what it refers to constitutional directives observance from whom must be extract the maximum efficiency. Established the premises on the possibility of the judicial control of the policies, the next step was the analysis of the normative structure of social rights, which can be principles and can be presented as subjective individual rights or collective rights. Soon after, the thesis clarified concerning the proportionality, that will have to be used for the solution of the collision between principles of fundamental rights. Premises concerning the limits of the judge discretional power had also been traced in the activity of control of the policies. The study also discussed about the institute of the possible resource, commonly seen as an external restraint to the fundamental right; as well as the judicial control of the administrative discretional power. Obligatoriness of the sentence rational motivation has been also debated, either for the publicity of the decisions, either for the adversary system, understood as a right of influence and a duty of debates (judge). It’s been also understood that jurisprudence takes part as a primary source of law, when assume the role of enhancing the fundamental social rights content. After that, it’s been also analyzed some topics concerned to the procedural judicial control of policies, in comparison to decisions pronounced by diverse courts of the country.